Assessing the state of forensic support to criminal investigations in Ghana: A case study in the Greater Accra Region - Sulley, Yahaya, Sumara; Quansah, Lydia (My University, 2020)
Forensic science applications in criminal investigation are very profound to crime resolution. However, there is a wide gap between the application of specialist skills and public knowledge and awareness of forensic science in criminal investigations and it has generated complex practical problems in justice delivery in Ghana. The study attempts to assess the state of forensic support to criminal investigations by accessing public knowledge and perception of forensic science in Ghana. To this account, an elaborate and tortuous survey was conducted using 200 consented respondents in selected neighborhoods in Accra based on homogeneity, population density, economic or industrial activities, and the nature of crime and police activities. The survey included face to face interviews, questionnaire responding, and random phone calls. The final data which was subjected to a simple linear regression model were analyzed with STATA 13. The study revealed that indeed, forensic science in Ghana has "gone dark" as 165(82.5%) who had a formal education of various levels had very limited knowledge about forensic science and procedures. The majority of the respondents 179(89.5%) had no idea about forensics and for that matter lacked awareness of forensics in Ghana before the research while the state of forensics in Ghana was rated on the scale of good (10.5%), bad (81.5%) and very bad (8%) out of the 200 respondents with the respondent level of education, perception, knowledge, and awareness of forensic science and support significantly impacting the wellbeing of the research. The findings of this study call for government and respective stakeholders and policymakers of various institutions, and the adversarial system of Ghana to prioritize the need for forensic science. This is to support criminal investigations to assure the Ghanaian citizens of their safety, security, and fundamental Human rights to justice.
Keywords: criminal investigations; criminal justice system; forensics science; forensic support; fundamental human rights; Ghana; Justice delivery